Carnivore Protoparvovirus-1 Associated With an Outbreak of Hemorrhagic Gastroenteritis in Small Indian Civets. Issue 5 (September 2020) - Chaiyasak, Surangkanang; Piewbang, Chutchai; Banlunara, Wijit; Techangamsuwan, Somporn
Carnivore protoparvovirus-1 (CPPV-1) infection has been reported frequently in both domestic and wildlife species including wild carnivores. Fifty-five captive small Indian civets ( Viverricula indica ), farmed for perfume production in Eastern Thailand, showed clinical signs of acute bloody diarrhea, anorexia, vomiting, circling, and seizures. The disease spread within the farm and resulted in the death of 38 of the 55 civets (69% mortality) within a month. Fecal swabs were collected from the 17 surviving civets, and necropsy was performed on 7 of the dead civets. Pathologic findings were severe hemorrhagic gastroenteritis with generalized lymphadenopathy. CPPV-1 was identified in both fecal swabs and postmortem samples by species-specific polymerase chain reaction. Further whole-gene sequencing and restriction fragment length polymorphism analysis suggested feline panleukopenia virus (FPV) as the causative agent. The viral tropism and tissue distribution were confirmed by immunohistochemistry, with immunolabeling in the cytoplasm and nucleus of small intestinal crypt epithelial cells, villous enterocytes, histiocytes in lymphoid tissues, myenteric nerve plexuses, and cerebral and cerebellar neurons. Phylogenetic analysis of civet-derived CPPV-1 indicated a genetic similarity close to the FPV HH-1/86 strain detected in a jaguar ( Panthera onca ) in China. To our knowledge, this mass die-off of civets is the first evidence of disease associated with CPPV-1 infection in the subfamily Viverrinae . These findings support the multi-host range of parvovirus infection and raises awareness for CPPV-1 disease outbreaks in wildlife species.